Jamu as a Healthy Solution for Travelers: The Initiative of DPD Aspetri East Java at the Health Post in Purabaya Terminal - Wibowo, Teguh Setiawan; Larasaty, Hartaty; Nawawi, Imam (Westscience Press, 2025)
Long journeys often cause fatigue and a decrease in immune function, especially for public transportation users. Jamu, as a heritage of herbal medicine from the Indonesian archipelago, holds great potential in maintaining health and enhancing stamina during travel. This community service activity aims to introduce and distribute jamu as a healthy solution for travelers through the initiative of DPD Aspetri Jawa Timur at the Health Post in Purabaya Terminal. The activity includes education on the benefits of jamu, free distribution of jamu, and herbal-based health consultations for passengers and terminal visitors. The results of the activity show that the majority of beneficiaries responded positively to the program, with an increased understanding of the benefits of jamu in maintaining health during travel. This activity is expected to serve as a model for promoting herbal-based health in other public facilities.